The Influence of Transparency Procedures on Attaining Digital Justice: A Survey at the Central Library of the University of Karbala - Dr.Omaima Hameed Aladilee (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Transparency has become a central principle in modern information institutions, particularly university libraries that aim to provide equitable access to knowledge and digital resources. Specific Background: In the context of digital transformation, libraries are increasingly expected to implement transparent policies and procedures to ensure that users can access information services fairly and efficiently. Knowledge Gap: Despite growing attention to transparency and digital inclusion in library science, limited empirical studies have examined how transparency practices relate to digital justice within university library environments. Aims: This study investigates the relationship between transparency practices and the achievement of digital justice in the Central Library of the University of Karbala. Results: Using a survey method with 183 beneficiaries and statistical analysis including structural equation modeling, the findings demonstrate a significant relationship between transparency practices and digital justice, with transparency explaining approximately 45% of the variance in digital justice outcomes. Dimensions such as information accessibility, accountability, and community participation show notable associations with equitable digital service provision. Novelty: The study integrates the concepts of organizational transparency and digital justice within a single empirical framework in the context of an academic library. Implications: The findings provide evidence that transparent governance, accessible information channels, and participatory practices can support equitable digital access and improve users’ experiences with library services in higher education institutions. Highlights: Transparency dimensions demonstrate measurable relationships with equitable digital access in library services. Accessibility and accountability mechanisms receive stronger user responses than disclosure practices. Institutional governance practices support inclusive digital resource availability for library beneficiaries. Keywords: Transparency Practices, Digital Justice, Academic Libraries, Information Accessibility, Digital Inclusion